Underground structures : design and instrumentation - Sinha, R. S. (Developments in geotechnical engineering, 1989)
This book presents the most up to date information relevant to the design and instrumentation of underground structures. The structure might be a tunnel, shaft, cavern, or pressure unit, or a combination thereof. Empirical, rational, numerical, convergence and confinement, and discontinuity analysis methods are treated comprehensively. Special chapters are devoted to underground structures in rock burst, swelling, squeezing, and seismic zones. Water control, instrumentation, and tunneling through soft ground are also treated extensively. Sections on the design of pressure tunnels, shafts, caverns, shotcreting, water control, and soft ground tunnels are informative and authoritative. Worked examples are included on the design of rock tunnels, soft ground tunnels, and the treatment of underground structures through difficult ground. Extensive references are provided, and figures, sketches and photographs aid presentation. Important tables on planning, and case histories, allow the reader to build confidence in his design of underground structures. The book will be beneficial to civil, structural, geotechnical and mining engineers, geologists, and planners and managers associated with the design and construction of underground structures.